Influência da matriz de esmalte dentário (Emdogain) e do fluoreto de sódio sobre o processo de reparo em reimplante mediato: análise histológica e histométrica em ratos - Carvalho, Roberta Martinelli [UNESP] (2003)
Although it has already been shown Emdogain® promotes periodontal regeneration in treatment of intrabony periodontal defects, there is limited information concerning its regenerative capacity to delayed replanted teeth. Aiming to evaluate the changes in the periodontal healing of these teeth after its use, the central incisors of 24 rats (Rattus norvegicus, albinus, Wistar) were extracted and left on bench for 6 hours. After that, the dental papilla and the enamel organ were sectioned for the pulp removal through a retrograde via. The channels were irrigated with 1% sodium hypochlorite. The animals were divided into two groups: Group I, in which root surface had been treated with 1% sodium hypochlorite for 10 minutes (changing the solution every 5 minutes), and rinsed with saline for another 10 minutes, before immersed in 2% sodium fluoride phosphate acidulated for 10 minutes; Group II, in which root surfaces had been treated same way described above, except for the application of Emdogain® instead of fluoride. The teeth were filled with calcium hydroxide (Group II right before the Emdogain®'s application) and replanted. All animals received antibiotic therapy. Rats were killed 10 and 60 days after replantation. Histological and histometrical analysis showed Group I presented the largest areas of replacement resorption while Group II preserved cementum integrity and showed more extensive ankylotic areas than replacement resorption. Emdogain wasn't able to avoid dentoalveolar ankylosis in delayed tooth replantation